IPTEKS Bagi Masyarakat Kelompok Pembudidaya Lobster - Muhammad Junaidi; Ayu Adhita Damayanti; Bagus Dwi Hari Setyono; Nunik Cokrowati (Pascasarjana Universitas Mataram, 2020)
Due to the increasing demand for lobster raw materials, the demand for lobster seeds continues to increase. UD Sari Laut as a lobster farming group is struggling to meet the demand for lobsters due to the limited number of floating net cages (In Indonesian called KJA) for running lobster seed farms. In an intensive lobster farming business, it is estimated that about 70% of production costs come from feed costs. The aim of this activity is to implement waste fishing technology using floating maps to increase the scale of lobster farming and reduce feed purchase costs. The activity method used is the demonstration plot directly with activity partners with activity stages including preparation for the purchase of floating net cages (KJA) and floating maps, group training, coaching, monitoring and evaluation. The result of this activity was the addition of KJA plots to 9 plots, previously only 6 plots giving a positive value to UD Sari Laut. Besides being able to house about 1,350 lobster seeds, with the addition of KJA plots it can also be used for lobster seed nursery operations with a profit of Rp. 2,970,000/month. The results of the garbage floating cards purchasing activity to meet the need for comprehensive lobster culture feed in KJA provides positive value for KUB Cinta Bahari. Where before having a floating card, the growers usually bought waste fish from fishermen around the site. The cost of buying waste fish ranges from Rp. 30,000 - Rp 50,000, depending on the season and the size of the business. So, with the operation of the floating card, the production cost of feed can be reduced. The existence of this floating card provides additional income, selling fish of high commercial value in the market. The conclusion of this activity is that this activity has a positive value for the target group, by increasing the number of floating net cages for the storage and breeding of lobster seeds and the availability of floating card cages.